Recommendations from GEC ESTRO Breast Cancer Working Group (II): Target definition and target delineation for accelerated or boost partial breast irradiation using multicatheter interstitial brachytherapy after breast conserving open cavity surgery - Major, Tibor; Gutierrez, Cristina; Guix, Benjamin; Van Limbergen, Erik; Strnad, Vratislav; Polgar, Csaba (Radiotherapy and Oncology, 2016)
To prepare guidelines for target definition and delineations after open cavity breast conserving surgery in accelerated partial breast irradiations or boost treatments using multicatheter interstitial brachytherapy based on the consensus of the Breast Working Group of GEC-ESTRO.Following a study on interobserver variations of target volume delineation in multicatheter breast brachytherapy after open cavity surgery and a number of discussions in consensus meetings these guidelines were worked out by experts on the field.(1) Consistent windowing has to be used for proper cavity visualization. (2) The cavity visualization score has to be at least 3 in order to minimize the interobserver variations of target definition. (3) At delineation of surgical cavity only the homogeneous part of the postoperative seroma has to be included in the contours and protrusions or sharp irregularities have to be excluded. When surgical clips are present, they have to be surrounded by the contour with close contact. (4) CTV is created from the outlined surgical cavity with a nonisotropic geometrical extension. In each direction the safety margin is calculated by taking into account the size of the free resection margin. The total size of safety margin is always 20mm which is the sum of the surgical and added safety margins. CTV is limited to chest wall/pectoral muscles and 5mm below the skin surface.Following these guidelines the target volume definition in breast brachytherapy after open cavity surgery is expected to be accomplished in more consistent way with low interobserver variations.
EVALuna2:18352